Psychological discomfort, resilience and academic performance in students characterized as displaced (Encuentros, 2021)
The objective of the research is to determine the relationship between psychological distress, resilience and academic performance in students belonging to the population of victims of the armed conflict of the Popular University of Cesar. The methodology was quantitative, correlational, non-experimental, cross-sectional in scope, where it was applied to a sample of 170 students belonging to the population victim of the conflict, the instruments applied were the SCL-90-R symptom checklist (Derogatis, 1983) and the resilience test of Wagnild and Young in (1987), record of students' grades. The results were that 75% of the participants were female, the mostprevalent academic averages were 4.0 to 4.5, although 14% of the population was evidenced with an average of 3.0 - 3.5. High resilience prevailed with 61%, and the symptoms of psychoticism, obsessions and compulsions, interpersonal sensitivity, phobic anxiety and depression were those that obtained the highest scores in terms of risk status in the population. It was concluded with a highly positive negative correlation between psychological distress and resilience, and a significant negative correlation between phobic anxiety and academic performance.
Keywords: Psychological Discomfort, Resilience, academic performance, displaced persons, victims, students.